Improving Transport Logistics by Aligning Long Combination Vehicles via Mobile Hub & Spoke Systems - Peter C. Schuur; Christopher N. Kellersmann (Logistics)
Background: The purpose of this paper is to develop a generic transport system for same-day delivery that is suitable for matching long-distance bulk distribution with local distribution. Methods: The innovative concepts of this research entail the introduction of mobile hub (MH) networks in combination with long combination vehicles (LCVs). LCVs are trucks with an additional loading capacity of 50% compared to standard trucks. Mobile hubs allow switching trailers at any suitable location at any time. They increase flexibility and yield savings in time and costs. On top of that, they reduce the number of driver hours needed. In our LCV-MH concept, standard trucks are initially—at their home base—combined to LCVs, which drive a considerable distance, but are eventually, at a mobile hub in the vicinity of the customers, broken down again into standard trucks heading for the customers. Results: We illustrate the practical relevance of our ideas by a case study based upon actual and accurate data from practice. Here, we compare the LCV-MH concept with the strategy of using only LCVs. Conclusions: Next to yielding considerable cost savings, the LCV-MH concept makes it easier to generate routes that comply with the EU transport rules.